"The Base on Which Thy Greatness Stands": Self-Fashioning and the Grounds of the Past in The Prelude. Issue 2 (4th March 2019) - Guthrie, Bernadette
ABSTRACT: In this article, I argue that one of the "spots of time" in The Prelude, the gibbet mast on the moor episode, offers critics a new way to conceptualize how Romantic autobiography responds to the perceived groundlessness of modernity. I contend that, through the material ground of this spot, we can trace the remnants of past "grounds" for authority, belief, and subjectivity that subsist even after they have ceased to be foundational. The site of the gibbet mast demonstrates how the illegibility of these grounds causes them to function as ciphers that simultaneously underscore both the past's inaccessibility and its material persistence. This account of the gibbet mast thus challenges critical accounts of the "spots of time" as paradigmatic instances of autobiographical self-fashioning.